Peran Media Instagram dalam Memasarkan Produk Fashion Dollies - Lucy Pujasari Supratman; Mochammad Rachmansyah (Jurnal Studi Komunikasi dan Media, 2020)
Indonesian internet users dominate access to chat services and social media, one of which is Instagram. The business began to enter the medium that is have much audiences. This phenomenon is used by Dollies through Instagram @wearedollies as a product marketing communication medium. This study aims to describe comprehensively the role of social media content in marketing Dollies products via Instagram @wearedollies. The analysis was carried out using marketing mix and promotion mix theory which is connected with the @wearedollies instagram contents. Descriptive qualitative paradigm is used to understand all phenomenons that occured. The result is the Instagram content @wearedollies used all elements of the promotion mix with diverse roles. The content that appeared consists of Instagram profiles, product photos and videos, captions, feedback comments, and direct messages for existence roles, repost and testimonials content for engagement roles, open reseller, discounts, and open orders content for sales roles, as well as endorse and giveaway content traffic roles. Pengguna internet Indonesia mendominasi akses layanan chatting dan media sosial, salah satunya instagram. Bisnis pun mulai memasuki ruang yang banyak diminati khalayak tersebut. Fenomena ini dimanfaatkan Dollies melalui instagram @wearedollies sebagai media komunikasi pemasaran produknya. Penelitian ini bertujuan untuk mendeskripsikan secara komprehensif mengenai peran konten media sosial dalam pemasaran produk Dollies melalui instagram @wearedollies. Analisis dilakukan dengan menggunakan teori bauran pemasaran dan promosi yang dikaitkan dengan konten instagram @wearedollies. Paradigma kualitatif deskriptif digunakan untuk memahami rincian fenomena yang terjadi. Hasil dari penelitian ini adalah konten instagram @wearedollies menggunakan seluruh elemen bauran promosi dengan peran yang beragam. Konten yang dimunculkan terdiri dari profil instagram, foto dan video produk, caption, feedback komentar, dan direct message untuk peran eksistensi, konten repost dan testimoni untuk peran engagement, konten open reseller, diskon, dan open order untuk peran penjualan, serta konten endorse dan giveaway untuk peran traffic.